Prognostic performance of the neutrophil-lymphocyte ratio for early complications following sleeve gastrectomy - Huertas-Campos, Luz F. (2025)
Aim: To evaluate the prognostic performance of the preoperative neutrophil-to-lymphocyte ratio (NLR) for early complications following sleeve gastrectomy. Methods: A retrospective cohort study was conducted by analyzing the institutional database of a bariatric clinic from 2017 to 2020. The neutrophil-to-lymphocyte ratio was determined from the preoperative blood count. The area under the curve (AUC) was calculated to determine the performance of the preoperative NLR for early postoperative complications following sleeve gastrectomy. Results: Among the 387 patients who underwent sleeve gastrectomy, 45 experienced complications within the first 30 postoperative days (11.6%). The AUC for NLR as a predictor of overall early complications after sleeve gastrectomy was 0.42, and for severe complications, it was 0.39. Conclusion: The preoperative NLR does not perform well as a prognostic indicator for early complications from sleeve gastrectomy.